The Case for good enough global governance - Patrick, Stewart (2014)
Argues that the future will not see the renovation or the construction of a glistening new international architecture but rather the continued spread of an unattractive but adaptable multilateral sprawl that delivers a partial measure of international cooperation through a welter of informal arrangements and piecemeal approaches. Posits that even though global disorder is here to stay, the challenge is to make it work as well as possible.